2005
DOI: 10.1536/ihj.46.1015
|View full text |Cite|
|
Sign up to set email alerts
|

<b>Blood B-Type Natriuretic Peptide Changes in Different Periods and Different Cardiac Pacing Modes</b>

Abstract: SUMMARYTo observe blood B-type natriuretic peptide (BNP) level changes and the clinical implications in different periods and different cardiac pacing modes, the BNP levels of 105 patients with permanent cardiac pacing were assayed before pacemaker implantation and 1 day, 1 week, 1 month, 3 months, 6 months, and 9 months postoperatively. BNP level changes were compared in different periods and during different pacing modes. DDD(R) pacing mode was performed in 32 patients for 9 months and then changed to AAI(R)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Due to maintaining sequential atrioventricular conduction in physiologic pacing, it produces beneficial effects on patients’ hemodynamics. It has been reported that NP levels will change in patients with permanent cardiac pacing 8–10 ; nevertheless, in fact, we do not exactly know how BNP and NT‐proBNP levels change in different pacing modes, and we do not accurately know if physiologic pacing can really reduce BNP and NT‐proBNP levels, either.…”
Section: Np Levels and Permanent Cardiac Pacingmentioning
confidence: 96%
See 2 more Smart Citations
“…Due to maintaining sequential atrioventricular conduction in physiologic pacing, it produces beneficial effects on patients’ hemodynamics. It has been reported that NP levels will change in patients with permanent cardiac pacing 8–10 ; nevertheless, in fact, we do not exactly know how BNP and NT‐proBNP levels change in different pacing modes, and we do not accurately know if physiologic pacing can really reduce BNP and NT‐proBNP levels, either.…”
Section: Np Levels and Permanent Cardiac Pacingmentioning
confidence: 96%
“…The results illustrated that BNP levels in VVIR pacing were notably higher than those in DDDR pacing. The first author and the third author of this article 10 assayed BNP levels in 105 patients with permanent cardiac pacing during preoperation and 9 months postoperatively (Table IV). BNP levels in patients with NYHA heart functional class I to II showed no significant change in physiologic and nonphysiologic pacing during preoperation and 9 months postoperatively (Fig.…”
Section: Np Levels and Permanent Cardiac Pacingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Wang et al in 105 patients with DDD/R and VVI/R pacemakers found a clear relationship between BNP levels, mode of pacing, and NYHA class [31].…”
Section: Medical Studies/studia Medyczne 2015; 31/4mentioning
confidence: 98%
“…Furthermore, BNP levels reflect hemodynamic changes elicited by different pacing modes, and BNP levels are significantly higher during asynchronous ventricular pacing than during atrioventricular sequential pacing. [1012] It has been reported that BNP levels will change in patients with permanent cardiac pacing;[1013] nevertheless, in fact, we do not exactly know how BNP levels change in different pacing sites, and we do not accurately know if RV septal pacing can really reduce BNP levels.…”
Section: Introductionmentioning
confidence: 99%